2011
DOI: 10.1111/j.1365-2583.2011.01112.x
|View full text |Cite|
|
Sign up to set email alerts
|

The Anopheles gambiae alpha‐tubulin‐1b promoter directs neuronal, testes and developing imaginal tissue specific expression and is a sensitive enhancer detector

Abstract: A knowledge gap in mosquito functional genetic analysis is the dearth of characterized regulatory regions that can target tissue specific transgene expression. To broaden the tools available, a promoter region of the Anopheles gambiaeα-tubulin1b gene has been assayed following fusion to the green fluorescent protein (GFP) reporter gene and stable transformation of An. gambiae. In eight transgenic lines, the Angtub α1b regulatory region directed a core profile of tissue specific expression in the head, chordoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Similar frequencies of intragenic insertions have been achieved in other series of piggyBac mediated transformation of An. gambiae [52] which suggests that high throughput mutagenesis studies would be feasible if other aspects of transgenic mosquito selection, maintenance and preservation were optimised. Two lines, Wby and Xnt, which carry transgene insertions into orthologues of the Drosophila Furin2 and dachs genes have been deposited with the Malaria Research and Reference Reagent Resource Center (MR4) to enable potential phenotypes from gene knock downs or hypomorphic alleles to be examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Similar frequencies of intragenic insertions have been achieved in other series of piggyBac mediated transformation of An. gambiae [52] which suggests that high throughput mutagenesis studies would be feasible if other aspects of transgenic mosquito selection, maintenance and preservation were optimised. Two lines, Wby and Xnt, which carry transgene insertions into orthologues of the Drosophila Furin2 and dachs genes have been deposited with the Malaria Research and Reference Reagent Resource Center (MR4) to enable potential phenotypes from gene knock downs or hypomorphic alleles to be examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , only two lines from a total number of nine transgenic mosquitoes lines robustly expressed the EGFP reporter (Franz et al, 2011). Lycett et al (2012) found that the alpha-tubulin-1b gene promoter directed transgene expression in the head, ventral nerve cord and testes of one An. gambiae transgenic line; however, expression of the same transgene was observed in larval and adult muscles, fat body, cuticle and midgut secretory cells of a different transgenic line.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, structural and mutation analyses of testis-specific tubulin isotypes leading to dysfunctional axonemal assemblies and male-sterile genotypes, confirmed the fundamental role of most testis-specific tubulins in the correct assembly of sperm axoneme (Fackenthal et al, 1995;Hutchens et al, 1997). Interestingly, it is currently known that expression of tissue-specific tubulins is mediated by their gene promoters (Bo and Wensink, 1989), a knowledge that has become useful in transgenic technology for biological control of pests and research inducing directed tissue-specific expression of transgenes using native promoters as those in α-and β-tubulins (Siebert et al, 2008;Zimowska et al, 2009;Lycett et al, 2011). We were unable to find in the available literature any testis-specific tubulin in mollusks.…”
Section: Tub-α Expression Is Testis-and Muscle-specificmentioning
confidence: 96%
“…This is the case of the functional hermaphrodite scallop N. subnodosus. In this organism it is expected that gonad development will modulate the whole transcriptional activity (including many housekeeping genes) in a sex-biased manner (Lu and Wu, 2011). Whereas no studies have been performed on the functional hermaphrodite scallops regarding the definition of stably expressed genes or gonad sex differentially expressed genes, studies do exist in the model nematode Caenorhabditis elegans and in some hermaphrodite plants indicating differences in expression between male, hermaphrodite and female sexual stages and organs (Jiang et al, 2001;Silveira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%